Optimized management strategy increased grain yield, promoted nitrogen balance, and improved water productivity in winter wheat - Xu, Haicheng; Liu, Mei; Tang, Yuhai; Zhao, Fei; Cao, Wenchao; He, Mingrong; Peng, Dianliang; Dai, Xinglong (Frontiers in Plant Science, 2023)
The increasing costs of agricultural production and environmental concerns reinforce the need to reduce resource inputs. Improvements in nitrogen use efficiency (NUE) and water productivity (WP) are critical for sustainable agriculture. We aimed to optimize management strategy to increase wheat grain yield, promote N balance, and improve NUE and WP. A three-year experiment was conducted with four integrated treatments including conventional practice treatment (CP); improvement of conventional practice treatment (ICP); high-yield management treatment (HY), which aimed for maximizing grain yield regardless of resource inputs cost; integrated soil and crop system management treatment (ISM), which aimed for testing an optimal combination of sowing date, seeding rate, fertilization and irrigation management. The average grain yield for ISM was 95.86% of that for HY and was 5.99% and 21.72% higher than that for ICP and CP, respectively. ISM promoted N balance as relatively higher aboveground N uptake (AGN), lower inorganic N residue (INR), and lowest inorganic N loss (INL). The average NUE for ISM was 4.15% lower than that for ICP and was remarkably higher than that for HY and CP by 26.36% and 52.37%, respectively. The increased soil water consumption under ISM was mainly due to its increased root length density (RLD). Along with a high level of grain yield, ISM obtained a relatively adequate water supply due to the effective use of soil water storage, thereby increasing the average WP by 3.63%–38.10% in comparison with other integrated management treatments. These results demonstrated that optimized management strategy (appropriately delaying sowing date, increasing seeding rate, optimizing fertilization and irrigation management) used under ISM could promote N balance and improve WP while increasing grain yield and NUE in winter wheat. Therefore, ISM can be considered a recommendable management strategy in the target region.